Escuela nueva en Argentina y Brasil Visiones compartidas - GVIRTZ, Silvina comp. (MIÑO Y DAVILA, 1996)
Contiene colaboradores: MENIN, Ovide; NUNEZ, Clarise; NARODOWSKI, Mariano; CHAGAS DE CARVALHO, Marta; GONCALVEZ VIDAL, Diana; ROITENBURD, Silvia